PERINTISAN UNIT USAHA PENGELOLAAN SAMPAH BUMDESA PANYANGGAR DESA WISATA CIPTA KARYA - Shanti Veronica br Siahaan; Sira Albina; Petrus Benny; Deli Deli; Serli Aprianti; Oktoberni Oktoberni; Sofia Anggriani; Novena Gloria Dara Tarigas; Rezza Pana Kontesa; Angga Domeos Manggara (JMM (Jurnal Masyarakat Mandiri), 2023)
Abstrak: Pengetahuan dan pengalaman serta keseriusan dalam menangani sampah diperlukan agar sampah tidak hanya menjadi masalah namun dapat bermanfaat melalui program 3R (Reduce, Reuse, Recycle) dan pelaksanaan sistem bank sampah. Oleh karena itu melalui program Matching Fund kedaireka tahun 2022 Institut Shanti Bhuana bekerjasama dengan BUMDesa Panyanggar Desa Cipta Karya, Kabupaten Bengkayang. melakukan serangkaian kegiatan untuk meningkatkan kepedulian dan kemampuan masyarakat desa untuk dapat melihat potensi nilai sosial dan nilai ekonomis penanganan sampah dan mempersiapkan SDM untuk pengelolaan sampah melalui kegiatan ceramah, diskusi, pelatihan, pendampingan disertai evaluasi kegiatan yang dilaksanakan mulai bulan September-Desember 2022, dengan jumlah total peserta kegiatan mencapai 250 orang yang diikuti oleh Pemerintahan Desa Cipta Karya, pengurus unit pengelola sampah BABE, perwakilan masyarakat desa dan mahasiswa Institut Shanti Bhuana. . Hasil yang dicapai dari kegiatan ini adalah terbentuknya unit pengelolaan sampah BABE serta peningkatan kemampuan peserta kegiatan dalam pemahaman nilai sosial dan nilai ekonomis dari sampah melalui kegiatan pemilahan sampah sesuai jenisnya, sistem bank sampah, dan berbagai manfaat pengelolaan sampah yang dapat dilihat melalui aktivitas Jumat Bersih, laporan kegiatan unit pengelolaan sampah BABE dan produk yang dihasilkan dari pengolahan pupuk cair organik dan sampah plastik. Abstract: Knowledge and experience as well as seriousness in dealing with waste are needed so that waste is not only a problem but can be beneficial through the 3R program (Reduce, Reuse, Recycle) and the implementation of a waste bank system. Therefore, through the Matching Fund Kedaireka program in 2022, the Shanti Bhuana Institute is collaborating with the BUMDESa Panyanggar, Cipta Karya Village, Bengkayang Regency. conducted a series of lectures, discussions, training, and mentoring along with an evaluation of activities carried out from September-December 2022, with a total number of activity participants reaching 250 people who were attended by Cipta Karya Village Government, administrators of the BABE waste management unit, village community representatives and students of Institute Shanti Bhuana. The results achieved from this activity were the formation of a BABE waste management unit and an increase in the ability of activity participants to understand the social value and economic value of waste through activities of sorting waste according to its type, a waste bank system, and various benefits of waste management which can be seen through Clean Friday activities, report on the activities of the BABE waste management unit and products resulting from the processing of organic liquid fertilizer and plastic waste. Knowledge and experience as well as seriousness in dealing with waste are needed so that waste is not only a problem but can be beneficial through the 3R program (Reduce, Reuse, Recycle) and the implementation of a waste bank system. Therefore, through the matching fund program in 2022, Institute Shanti Bhuana in collaboration with BUMDesa Panyanggar Cipta Karya Village, Bengkayang is carrying out a series of activities to increase the awareness and ability of the village community to be able to see the potential social and economic value in waste and prepare human resources to handle waste management. through lectures, discussions, training, mentoring and evaluation of activities carried out from September-December 2022. The results achieved from this activity were the formation waste management unit “BABE” and an increase the participants ability in understanding the social and economic value that can still be obtained from waste through activities segregation of waste according to its type, waste bank system, and various benefits of waste management.